2016
DOI: 10.1186/s13756-016-0103-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and molecular epidemiology of extended-spectrum beta-lactamase-producing Enterobacteriaceae from intensive care units at Hamad Medical Corporation, Qatar

Abstract: BackgroundThe emergence of extended-spectrum beta-lactamase (ESBL)-producing isolates has important clinical and therapeutic implications. High prevalence of ESBL-producing Enterobacteriaceae has been reported in the literature for clinical samples from a variety of infection sites. The present study was undertaken to evaluate the prevalence of ESBL-producing Enterobacteriaceae, and to perform molecular characterization and antimicrobial susceptibility testing of clinical isolates from patients admitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
24
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
(37 reference statements)
10
24
3
Order By: Relevance
“…Out of the 13 Klebsiella isolates, 9 (69.23%) were phenotypically positive for ESBL production, and out of the 11 E. coli isolates, 6 (54.55%) were phenotypically positive for ESBL production ( Table 3). Similar findings were obtained by Tajeddin et al [11] from Iran who reported 51.5% of Klebsiella and 77.8% of E.coli isolates to be ESBL positive, as well as Ahmed et al [47] from Qatar who ascertained 51.4% of Klebsiella isolates to be ESBL positive. In accordance with our findings, literature from Uganda and the United Kingdom also established Klebsiella species as the most frequent ESBL producers [9,39].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Out of the 13 Klebsiella isolates, 9 (69.23%) were phenotypically positive for ESBL production, and out of the 11 E. coli isolates, 6 (54.55%) were phenotypically positive for ESBL production ( Table 3). Similar findings were obtained by Tajeddin et al [11] from Iran who reported 51.5% of Klebsiella and 77.8% of E.coli isolates to be ESBL positive, as well as Ahmed et al [47] from Qatar who ascertained 51.4% of Klebsiella isolates to be ESBL positive. In accordance with our findings, literature from Uganda and the United Kingdom also established Klebsiella species as the most frequent ESBL producers [9,39].…”
Section: Resultssupporting
confidence: 87%
“…Imipenem was the most effective antimicrobial against E.coli, with a resistance rate of 9.09%. Resistance rates between the ranges 0% to 10% by E.coli to imipenem are globally comparable with several studies [9,[46][47][48]. Gentamicin proved to be the second most effective antimicrobial against both Klebsiella and E. coli isolates; including ESBL producers.…”
Section: Resultssupporting
confidence: 76%
“…The prevalence of CTX-M-1 had little difference among isolates from the two studied cities. Recent reports have shown a rapid and alarming dissemination of Enterobacteriaceae producing ESBLs of the CTX-M type in certain countries such as India [20], Cambodia [21], France [22], UK [23], Qatar [9] and Canada [24] that has become the most prevalent ESBL-type world-wide. A high prevalence and broad geographic distribution of CTX-M-producing E. coli and K. pneumonia nosocomial strains have been shown in Russia.…”
Section: Discussionmentioning
confidence: 99%
“…CTX-M-15 belongs to the CTX-M-1 cluster [7]. Phylogenetic studies suggest that bla CTX -M genes have evolved from chromosomal bla genes of Kluyvera sps [8,9]. bla CTX -M gene encodes a 291 amino acid enzyme although insertions and deletions in a few variants have sequences ranging from 282 to 292 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Modern data indicate a growing prevalence of ESBL's isolated from different patient groups globally [5][6][7][8][9][10]. However, neither single-nor multicenter studies have been conducted on ESBL-related hospital infections in Ukraine.…”
Section: Introductionmentioning
confidence: 99%